2021
DOI: 10.1021/acs.jmedchem.0c01768
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small-Molecule Antagonists of the PWWP Domain of NSD2

Abstract: Increased activity of the lysine methyltransferase NSD2 driven by translocation and activating mutations is associated with multiple myeloma and acute lymphoblastic leukemia, but no NSD2-targeting chemical probe has been reported to date. Here, we present the first antagonists that block the protein–protein interaction between the N-terminal PWWP domain of NSD2 and H3K36me2. Using virtual screening and experimental validation, we identified the small-molecule antagonist 3f, which binds to the NSD2-PWWP1 domain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Interestingly, as an alternative to SET domain NSD inhibitors, Berardi et al reported in silico derived small molecules that inhibited finger–finger interaction between PHDVC5HCH and C2HRNizp1 of NSD1. Likewise, some studies have reported the use of small molecules to interfere with the function of the PWWP domain as an alternative strategy for developing novel NSD inhibitors. , Compound 34 has been identified as the first potent small-molecule antagonist targeting the PWWP1 domain of NSD2, while another recent study reported the fragment-based discovery of a chemical probe 37 that displayed selective and potent antagonistic activity against the PWWP1 domains of NSD3 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, as an alternative to SET domain NSD inhibitors, Berardi et al reported in silico derived small molecules that inhibited finger–finger interaction between PHDVC5HCH and C2HRNizp1 of NSD1. Likewise, some studies have reported the use of small molecules to interfere with the function of the PWWP domain as an alternative strategy for developing novel NSD inhibitors. , Compound 34 has been identified as the first potent small-molecule antagonist targeting the PWWP1 domain of NSD2, while another recent study reported the fragment-based discovery of a chemical probe 37 that displayed selective and potent antagonistic activity against the PWWP1 domains of NSD3 …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, some studies have reported the use of small molecules to interfere with the function of the PWWP domain as an alternative strategy for developing novel NSD inhibitors. 26,32 Compound 34 has been identified as the first potent smallmolecule antagonist targeting the PWWP1 domain of NSD2, 32 while another recent study reported the fragment-based discovery of a chemical probe 37 that displayed selective and potent antagonistic activity against the PWWP1 domains of NSD3. 26 Recent studies indicate ongoing efforts to explore the structure and function of different NSD domains and PHD fingers to develop NSD-specific inhibitors as an alternative to catalytic SET domains of NSD methyltransferases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the Structural Genomics Consortium identified fragment 138 (Figure ) as a binder to the PWWP1 domain of NSD2 through virtual screening of ∼2 million commercially available compounds followed by SPR assays with 39 selected compounds . Further progress combined 2D similarity search of a virtual library of ∼8 million commercially available compounds generated by 3D shape matching with manually designed scaffold hopping.…”
Section: A Final Frontier: Methylation Readersmentioning
confidence: 96%